Augustine's Anthropological Hermeneutic and Political Thought in Dante Alighieri's De Monarchia - Paciorek, Piotr M. (Editorial Uniagustiniana, 2019)
This essay aims to evaluate the concept of peace that Dante Alighieri inscribed in De Monarchia, a work that is recognized as one of the major achievements of medieval political philosophy. Articulating peace as the main component of the Christian civilization of Western Europe, Dante remained under the influence of Aristotelian ethical and political thought, ancient Christian theologians, and the great authority of Augustine of Hippo. Since ancient thinkers believed that anthropological concepts should be subject to any socio-political investigation, peace, too, was examined from an anthropological perspective. Aristotle's anthropological hermeneutic employed the triad of body-soul-spirit to understand human nature and exposed the notion of universal peace to mean caritas, unity, and justice. Relying on Aristotle's triad and overall hermeneutic, Augustine's anthropological exploration of human nature is a metaphorical portrait of man in a constant struggle for harmony between soul and body, a harmony which could then be projected in society under governing nations. Guided by this initial examination of the Augustinian and Aristotelian hermeneutic, this essay explore De Monarchia in depth, so as to demonstrate Augustine's impact and inspiration on Dante's monarchical beliefs. The inquiry herein will specifically outline how Dante applied Augustine's concept of peace to his current socio-political system, both among individuals and particular communities.